2021
DOI: 10.33902/ijods.2021167818
|View full text |Cite
|
Sign up to set email alerts
|

Online learning amid COVID-19 pandemic: Perspectives of Bhutanese students

Abstract: The outbreak of COVID-19 has affected every aspects of human life around the globe. Education is one of the sectors that has been severely affected due to the outbreak of coronavirus. Schools in more than 190 countries got shut down to break the chain of coronavirus. Therefore, this study was aimed to examine the perspectives of Bhutanese students towards online learning amid COVID-19 pandemic. The study employed mixed method to triangulate the data and solidify the findings. A total participants of 200 day sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
3
11
0
1
Order By: Relevance
“…Over a third of studies reported students becoming cognitively disengaged (n = 30 studies, 37%), which was most commonly associated with students being 'confused' and having problems understanding or following lesson content (n = 15, 19%). In some cases, failing to keep up with lesson content was thought to be particularly challenging for more technical subjects (Dema et al, 2021). In an autoethnographic study, 'confusion' was attributed to a feeling of constant change, where students "felt 'more or less [like] an experiment [in which] things are changing very quickly.'…”
Section: Cognitive Disengagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Over a third of studies reported students becoming cognitively disengaged (n = 30 studies, 37%), which was most commonly associated with students being 'confused' and having problems understanding or following lesson content (n = 15, 19%). In some cases, failing to keep up with lesson content was thought to be particularly challenging for more technical subjects (Dema et al, 2021). In an autoethnographic study, 'confusion' was attributed to a feeling of constant change, where students "felt 'more or less [like] an experiment [in which] things are changing very quickly.'…”
Section: Cognitive Disengagementmentioning
confidence: 99%
“…A consequence of higher levels of disengagement was that students had lower levels of overall motivation (reported in 16 studies, 20%) and lower motivation was identified as being particularly problematic among lower achieving students in some studies (Nusser, 2021;Maelan et al, 2021;Pelikan et al, 2021). Although the explanations put forward for lower motivation among students were diffuse, a number of studies attributed issues with technology and internet connection as explanatory factors (Al Salman et al, 2021;Dema et al, 2021;Hodgen et al, 2020). Meanwhile, students in another study were observed to have lower levels of motivation as a result of broader uncertainty and concerns about the 'state of the world' (Yates et al, 2020) and a small number of studies also attributed lower levels of motivation to home environments that were not conducive to learning where other roles and duties that children have (e.g., caring for siblings, helping with family businesses) may have taken precedence (Azhari & Fajri, 2020;Sibanda & Mathwasa, 2021;Yates et al, 2020).…”
Section: Lower Motivation and Learning Lossmentioning
confidence: 99%
“…She felt that it was very demotivating since they could not fully concentrate on their studying. This issue also appeared in Wangdi et al (2021) study showing that 23.4% students were relieved from household chores and farming works during this time. Nevertheless, most of the students were supported by their family to go through home online learning (Khusyabaroh et al, 2018).…”
Section: Other Demotivating Factorsmentioning
confidence: 80%
“…It was harder for students coming from poor financial backgrounds to afford mobile data. As a consequence, they felt left under emotional stress and demotivated (Wangdi et al, 2021). Students also felt disturbed when noise came from an unmute mic during a live meeting.…”
Section: Other Demotivating Factorsmentioning
confidence: 99%
“…A research on Bhutan education during the crisis also highlighted the cost of internet which is beyond the ability of both students and teachers. It recommends the ministry of education of Bhutan provide a workshop for teachers to enhance their digital knowledge and to reduce the cost of the internet as much as possible [53].…”
Section: -Results and Discussionmentioning
confidence: 99%